Signing Ceremony NEPAD - WorldFish - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Signing Ceremony between NEPAD Dr. Ibrahim Mayaki (CEO, NEPAD Planning and Coordinating Agency) and Dr. Patrick Dugan (Deputy Director General - WorldFish). The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/